ANALISIS EFEKTIVITAS KINERJA TENAGA KEPENDIDIKAN BERBASIS TUPOKSI DI MTS RIYADLUL MA’ARIF KAWALU TASIKMALAYA - Komalasari, Imas; Apipah, Nur; Amini, Silvy Nuril; Al-Ayyubi, Sholahudin (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2023)
This study aims to analyze the effectiveness of the performance of education personnel based on their duties and functions. The research method uses a descriptive method with a qualitative approach. Data collection using observation, interview, and documentation techniques. The results of the study found that: 1) administration in the school consists of student administration, personnel administration, and financial administration. The education personnel work together to smooth the school administration even though they are not from a linear educational background; 2) administrative management is not yet optimal as seen from the fact that an annual program has not been made in each section; 3) development can be seen from the inputting/archiving of data from manually switched to digital; 4) supervision done by the head of the administrative office as a daily supervisor, the school principal once a month, and by the school supervisor during monitoring and evaluation and PKKM / S; and 5) services are provided to internal parties such as principals, teachers, and students as well as external services to the community and parents of students related to academic and non-academic matters.Penelitian ini bertujuan untuk menganalisis efektivitas kinerja tenaga kependidikan berbasis tupoksinya. Metode penelitian menggunakan metode deskriptif dengan pendekatan kualitatif. Pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian mendapatkan yaitu: 1) pengadministrasian di sekolah terdiri dari bagian administrasi kesiswaan, administrasi kepegawaian, dan administrasi keuangan. Para tenaga kependidikan melakukan kerja sama untuk kelancaran administrasi sekolah meskipun mereka bukan dari latar belakang pendidikan yang linear; 2) pengelolaan administrasi belum optimal terlihat dari belum dibuatnya program tahunan pada masing-masing bagian; 3) pengembangan terlihat dari penginputan/pengarsipan data yang semula secara manual beralih ke digital; 4) pengawasan dilakukan oleh kepala TU sebagai pengawas harian, kepala sekolah dilakukan satu bulan sekali, dan oleh pengawas sekolah ketika monev dan PKKM/S; dan 5) pelayanan diberikan kepada pihak internal seperti kepala sekolah, guru, dan siswa serta layanan eksternal kepada masyarakat dan orang tua/wali siswa berkaitan dengan hal akademik maupun non akademik.